UPAYA PENINGKATAN KEMAMPUAN MENGGIRING BOLA DALAM PERMAINAN BOLA BASKET MELALUI VARIASI LATIHAN DRIBLE PADA KELAS XI IPA III SMA NEGERI JATIROTO - Imam Hari Priyono (Lambung Mangkurat University, 2015)
In a Class Action Research has several goals as follows: (1) Want to know zig-zag variations can increase the motivation to learn drible on the game of basketball and (2) Want to know through the zig-zag variation in train with basketball can improve performance students.Research Sites SMAN Jatiroto. Classroom action research will be implemented in Class XI IPA.3. Time studies Semester Academic Year 2012/2013. Characteristics Students are very interested at all in games or basketball, this is evident in the student questionnaire to mememilih exstra curricular activities.Discussion of the results of the analysis can be described as follows: Exercise drible zig- zag was instrumental once against drible practice on the game of basketball. This is evident from analysis of increased capacity in table 5 and 6, both the increase in the number of students Very Good group of 3 to 11 with a percentage of 7.5% to 27.5%, for the group Good from 4 to 19 with a percentage of 10 % increase to 47.5%. So it can be concluded that (1) the exercise drible zig-zag was instrumental to increase student motivation and (2) the exercise drible zig-zag greatly contribute to improving the ability drible in the game of basketball. Keywords: Drible, basketball